P5.048 Reaching Women Through the Integration of HIV Testing into Public Service Sites: Experiences from the Department of Motor Vehicles and Income Maintenance Center in Washington, DC. (13th July 2013) - Fulwood-Wood, A; Hamilton, F; Brockington, S; George, L
Abstract : Background: Washington DC has an estimated HIV prevalence rate of 2.2% and only 50% may be aware of their infection. Using large volume public service venues may promote HIV testing and directly increase access to HIV testing, thereby increasing the number of residents who know their HIV status. Family and Medical Counseling Service, Inc. (FMCS) implemented a novel programme to provide HIV testing at the Department of Motor Vehicles (DMV) which provides driver's licence and automobile tag services to over 150, 000 residents annually. In 2011, we replicated this programme model in the Income Maintenance Center (IMC), the government office that provides residents with public benefits including financial assistance and health insurance. Methods: Dedicated project staff discusses the importance of HIV testing and offer the test to everyone awaiting DMV and IMC services. HIV testing is conducted in private offices inside the DMV and IMC, and all who test positive are immediately referred to care. We present data describing the HIV testing outcomes from the programme. Results: From October 2010 to October 2012, 247, 055 individuals were offered an HIV test, 23, 111 (9%) accepted, 21, 283 (93%) were tested, and 113 (0.5%) were positive. The majority of those tested were women 14, 667 (69%) between the ages of 23–40 (5, 463 or 37%). Of those tested, 33% (7, 023) were first time testers. Women accounted for 54% (3, 792) of all first time testers. Conclusions: Conducting HIV testing in high volume non-clinical settings, such as the DMV and IMC, is a feasible strategy to engage women in HIV counselling and testing services, including those who have never tested before. Expansion of this programme model to similar public service sites may be necessary to increase access to HIV testing services, encourage routine screening and increase the percentage of individuals in the general population who know their HIV status.